Tingkat Pengetahuan Tentang Anemia Dengan Kadar Hemoglobin (Hb) Ibu Hamil - Tri Maryani; Magdalena Vonni Lestari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: The incidence of anemia in Indonesia in 2013 reached 21.7%, while the incidence of anemia in DIYin 2011 amounted to 18.90%. Bantul Regency highest rank that is equal to 25.60%. Puskesmas Puskesmas DlingoII is the increased incidence of anemia from 2012 as much as 56.46% to 70.94% in 2013. The majority of the community education the average elementary school 3,716 people (2.3%) and a junior secondary education as muchas 1,903 people (1.2%) indicates a lack of knowledge.Objective: Knowing he relationship between the level of knowledge about anemia with hemoglobin levels in DlingoII Public Health Centre in 2014.Method: This type of research is an analytic observational with cross sectional study design. The study was conducted in Dlingo II Public Health Centre. The subjects were all pregnant women who come to Dlingo II Public HealthCentre who meet the inclusion and exclusion criteria. The total sample of 80 people. The research instrument witha questionnaire level of knowledge and Hb with Portable Digital Hemoglobin Analyzer.Results: The results of the level of knowledge about anemia pretty good (53.7%) and anemia hemoglobin levelsare not as much as 42.5%. Chi square test results obtained X2 is 2.6711 with a p-value is 0.045 (> 0.05).Conclusion: The study concluded that there is a relationship between the level of knowledge about anemia withhemoglobin levels in pregnant women.Keywords: Knowledge Level, Anemia, Hemoglobin, Pregnant Women.